Maternal exposure to butyl paraben impairs testicular structure and sperm quality on male rats - Guerra, Marina T. [UNESP]; Sanabria, Marciana [UNESP]; Leite, Gabriel A. A. [UNESP]; Borges, Cibele S. [UNESP]; Cucielo, Maira S. [UNESP]; Anselmo-Franci, Janete A.; Foster, W. G.; Kempinas, W. G. [UNESP] (Wiley, 2017)
Parabens are hormonally active chemicals widely used as preservatives in foods and are frequently detected in human fluids and tissues. Therefore, the objective of this study was to determine the effects of maternal butyl paraben (BP) exposure on male sexual development. Pregnant Wistar rats received corn oil (control group), or BP at doses of 10, 100, or 200 mg/kg, subcutaneously, from gestational day 12 until postnatal day 21. Our results demonstrated that developmental BP exposure significantly increased the number of adult Leydig cells and the circulating concentrations of testosterone and attenuated FSH and LH concentrations at 200 mg/kg. BP exposure adversely affected spermatogenesis kinetics at doses of 10 and 200 mg/kg and provoked a decrease in the immunostaining of EsR1 and AR at 200 mg/kg. The sperm motility was impaired at the 10 mg/kg dose, and sperm head abnormalities were increased in all BP dose groups. We suggest that BP impairs testicular structure and function in the rat, affecting sperm quality. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 1273–1289, 2017.
Keywords: male reproduction; paraben; sperm quality; testis